Magnetron sputtering deposition of GeSe thin films for solar cells. (December 2018) - Chen, Binwen; Chen, Guilin; Wang, Weihuang; Cai, Huiling; Yao, Liquan; Chen, Shuiyuan; Huang, Zhigao
Highlights: GeSe thin film was successfully prepared by sputtering deposition followed post-annealing. The effects of annealing temperatures on crystallinity and morphology of the GeSe films were systematically investigated. The GeSe device with FTO/CdS/GeSe/Carbon structure exhibits efficiency of 0.05% with Voc of 220 mV. Abstract: Germanium selenide (GeSe), a IV-VI chalcogenide containing earth-abundant and low-toxic elements, has attracted increasing interest as a potential absorber material for photovoltaics due to its excellent optical and electrical properties. In this work, a simple and effective magnetron sputtering method was proposed to deposite GeSe precursor thin films using GeSe alloy target. Subsequently, the as-deposited samples were post-annealed in vacuum atmosphere. The effects of different annealing temperatures on crystallinity, morphology and phase transformation of the as-prepared films were systematically investigated. It has been revealed that phase-pure and uniform GeSe thin films were obtained through the self-decomposition of slight GeSe2 impurity at 400 °C. Finally, a prototypical FTO/CdS/GeSe/C-Ag solar cell with 220 mV open circuit voltage and 0.05% power conversion efficiency was fabricated, which suggests the potential of sputtering processed GeSe thin film for low cost solar cell.